Comparative Metabolomic Profiling Reveals That Dysregulated Glycolysis Stemming from Lack of Salvage NAD(+) Biosynthesis Impairs Reproductive Development in Caenorhabditis elegans - Wang, Wenqing (J Biol Chem, 2015)
Temporal developmental progression is highly coordinated in Caenorhabditis elegans. However, loss of nicotinamidase PNC-1 activity slows reproductive development, uncoupling it from its typical progression relative to the soma. Using LC/MS we demonstrate that pnc-1 mutants do not salvage the nicotinamide released by NAD(+) consumers to resynthesize NAD(+), resulting in a reduction in global NAD(+) bioavailability. We manipulate NAD(+) levels to demonstrate that a minor deficit in NAD(+) availability is incompatible with a normal pace of gonad development. The NAD(+) deficit compromises NAD(+) consumer activity, but we surprisingly found no functional link between consumer activity and reproductive development. As a result we turned to a comparative metabolomics approach to identify the cause of the developmental phenotype. We reveal widespread metabolic perturbations, and using complementary pharmacological and genetic approaches, we demonstrate that a glycolytic block accounts for the slow pace of reproductive development. Interestingly, mitochondria are protected from both the deficiency in NAD(+) biosynthesis and the effects of reduced glycolytic output. We suggest that compensatory metabolic processes that maintain mitochondrial activity in the absence of efficient glycolysis are incompatible with the requirements for reproductive development, which requires high levels of cell division. In addition to demonstrating metabolic requirements for reproductive development, this work also has implications for understanding the mechanisms behind therapeutic interventions that target NAD(+) salvage biosynthesis for the purposes of inhibiting tumor growth.